Performance of fly ash-based inorganic polymer mortar with petroleum sludge ash - Kankia, M.U. (MDPI, 2021)
Petroleum sludge is a waste product resulting from petroleum industries and it is a major source of environmental pollution. Therefore, developing strategies aimed at reducing its environmental impact and enhance cleaner production are crucial for environmental mortar. Response surface methodology (RSM) was used in designing the experimental work. The variables considered were the amount of petroleum sludge ash (PSA) in weight percent and the ratio of sodium silicate to sodium hydroxide, while the concentration of sodium hydroxide was kept constant in the production of geopolymer mortar cured at a temperature of 60â¦ C for 20 h. The effects of PSA on density, compressive strength, flexural strength, water absorption, drying shrinkage, morphology, and pore size distribution were investigated. The addition of PSA in the mortar enhanced the mechanical properties significantly at an early age and 28 days of curing. Thus, PSA could be used as a precursor material in the production of geopolymer mortar for green construction sustainability. This study aimed to investigate the influence of PSA in geopolymer mortar. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.